Coupling passive sampling with in vitro bioassays and chemical analysis to understand combined effects of bioaccumulative chemicals in blood of marine turtles. (November 2015) - Jin, Ling; Escher, Beate I.; Limpus, Colin J.; Gaus, Caroline
Graphical abstract: Highlights: A quantitative PDMS partitioning system was designed to extract bioaccumulative chemicals from blood. Detected dioxin-like chemicals explained AhR-mediated activity of green turtle blood samples. Detected dioxin-like chemicals explained <0.4% of the oxidative stress response. Abstract: Conventional target analysis of biological samples such as blood limits our ability to understand mixture effects of chemicals. This study aimed to establish a rapid passive sampling technique using the polymer polydimethylsiloxane (PDMS) for exhaustive extraction of mixtures of neutral organic chemicals accumulated in blood of green turtles, in preparation for screening in in vitro bioassays. We designed a PDMS–blood partitioning system based on the partition coefficients of chemicals between PDMS and major blood components. The sampling kinetics of hydrophobic test chemicals (polychlorinated dibenzo- p -dioxins; PCDDs) from blood into PDMS were reasonably fast reaching steady state in <96 h. The geometric mean of the measured PDMS–blood partition coefficients for PCDDs, polychlorinated biphenyls (PCBs) and polybrominated diphenyl ethers (PBDEs) was 14 Lblood  kgPDMS −1 and showed little variability (95% confidence interval from 8.4 to 29) across a wide range of hydrophobicity (log  K ow 5.7–8.3). The mass transfer of these chemicals from 5 mL blood into 0.94 g PDMS was 62–84%, which is similar to analytical recoveries in conventional solvent extraction methods. The validated method was applied to 15 blood samples from green turtles with known concentrations of PCDD/Fs, dioxin-like PCBs, PBDEs and organochlorine pesticides. The quantified chemicals explained most of the dioxin-like activity (69–98%), but less than 0.4% of the oxidative stress response. The results demonstrate the applicability of PDMS-based passive sampling to extract bioaccumulative chemicals from blood as well as the value of in vitro bioassays for capturing the combined effects of unknown and known chemicals.